A FeS / FeOCl photocatalyst and its preparation method and application
FeS is generated by in-situ sulfurization of FeOCl, and a supported FeS/FeOCl photocatalyst is prepared, which solves the problem of acidic conditions required for organic wastewater treatment in the prior art, and achieves efficient, stable and environmentally friendly organic wastewater treatment effect.
Patent Information
- Application Number
- CN202410335685.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-03-22
AI Technical Summary
The prior art requires controlling acidic conditions when treating organic sewage, which increases the difficulty of operation and monitoring of the treatment system, and may generate a large amount of precipitates that require cleaning and further treatment.
FeOCl is used to generate FeS in situ vulcanization, and a supported FeS/FeOCl photocatalyst is prepared. By loading the FeS/FeOCl catalyst onto a glass matrix, a supported catalyst is formed.
It realizes efficient treatment of organic wastewater under neutral or near neutral conditions, improves Fenton reaction efficiency and photogenerated carrier separation efficiency, reduces precipitate generation, simplifies the treatment process, and improves the stability and recyclability of the catalyst.
Smart Images

Figure CN118988355B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a FeS / FeOCl photocatalyst and a preparation method and application thereof. Background Art
[0002] The amount of organic wastewater produced is huge. The processes used in current sewage treatment plants include, for example, microbial degradation, physical filtration adsorption sedimentation, and chemical advanced oxidation. As an advanced oxidation technology, Fenton technology can efficiently degrade a variety of organic pollutants, has high treatment efficiency and removal rate, and has been widely used in industrial wastewater and urban sewage treatment. However, its treatment process requires the control of acidic conditions (the common pH value is about 2-4), which increases the difficulty of operation and monitoring of the treatment system. A large amount of precipitate may be generated during the reaction, which needs to be cleaned and further treated.
[0003] Therefore, developing a method that can efficiently treat organic wastewater is of great significance to the development and industrial application of wastewater treatment technology. Summary of the invention
[0004] The purpose of the present invention is to solve the deficiencies of the prior art and provide a supported FeS / FeOCl photocatalyst and a preparation method and application thereof, specifically adopting the following technical solutions:
[0005] A method for preparing a FeS / FeOCl photocatalyst comprises the following steps:
[0006] Anhydrous FeCl3 is calcined in air, cooled to room temperature after calcination, centrifuged, washed with water, dried, and ground to obtain FeOCl; then FeOCl is dispersed in water and mixed with Na2S solution for reaction, centrifuged, washed with water, dried, and ground to obtain FeS / FeOCl photocatalyst; finally, FeS / FeOCl photocatalyst powder is placed in water and ultrasonically loaded on a glass substrate to finally obtain a supported FeS / FeOCl catalyst.
[0007] The present invention uses FeOCl to generate FeS by in-situ sulfurization to achieve catalyst surface modification, and can develop photocatalysts with ultra-high Fenton reaction efficiency and photogenerated carrier separation efficiency. Among them, FeOCl prepared using anhydrous FeCl3 has good stability, and Fe and Cl seepage is very little. Moreover, FeOCl is an iron-based material with a two-dimensional layered structure, which has Fenton catalytic activity, visible light catalytic activity (band gap ~1.78 eV) and has the characteristics of fast intralayer carrier transfer. On this basis, by in-situ sulfurization reduction of FeOCl, FeS is obtained to form a heterojunction, which is conducive to the separation of photogenerated electron-hole pairs. At the same time, the proportion of divalent iron sites is increased, which promotes the Fenton reaction and forms a more efficient FeS / FeOCl photocatalysis and Fenton catalyst. In addition, the preparation method of the catalyst in the present invention is simple, highly operable, and green and environmentally friendly, and is a new type of photocatalyst and Fenton catalyst that can be practically applied.
[0008] As a further preferred embodiment, FeS / FeOCl photocatalyst powder is placed in water and then ultrasonically loaded on a glass substrate to obtain a loaded FeS / FeOCl catalyst. The present invention obtains a loaded FeS / FeOCl photocatalyst by loading the FeS / FeOCl catalyst. Compared with the powder catalyst, the catalyst provided by the present invention retains the degradation efficiency well and can be better recycled, thereby avoiding the problem that the powder catalyst may be recycled unfavorably and cause secondary pollution damage to the water environment.
[0009] As a further preferred embodiment, the molar ratio of Na2S to FeOCl is 1:10-20. More preferably, the molar ratio of Na2S to FeOCl is 1:20. At a ratio of 1:20, better photo-assisted Fenton catalytic performance is exhibited.
[0010] As a further preferred embodiment, the calcination temperature is 380°C and the calcination time is 2.5 h.
[0011] As a further preferred embodiment, the above reaction is a magnetic stirring reaction, and the reaction time is 3 hours.
[0012] As a further preferred embodiment, the drying is performed by freeze vacuum drying, and the drying time is 24 h.
[0013] The present invention also provides a supported FeS / FeOCl photocatalyst prepared by the above preparation method, which can be used in photocatalytic or light-assisted Fenton reaction to degrade organic pollutants. The organic pollutants are ofloxacin, rhodamine B, bisphenol A, steroidal estrogen, ampicillin antibiotic, parachlorophenol insecticide or 2,4,6-trichlorophenol antibacterial agent.
[0014] The beneficial effects of the present invention are:
[0015] The preparation method of the present invention is simple, highly operable, and convenient to recycle and environmentally friendly. By in-situ sulfidation reduction of FeOCl to obtain FeS to form a heterojunction, it is beneficial to the separation of photogenerated electron-hole pairs. At the same time, the proportion of divalent iron sites is increased, which promotes the Fenton reaction and forms a more efficient FeS / FeOCl photocatalysis and Fenton catalyst. The supported FeS / FeOCl catalyst prepared by the present invention has ultra-high Fenton reaction efficiency and photogenerated carrier separation efficiency, and can be used in environmental treatment applications such as photocatalysis and light-assisted Fenton degradation of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 Shown are the X-ray diffraction patterns of FeOCl and FeS / FeOCl photocatalysts;
[0018] Figure 2 Shown are the XPS full spectra of FeOCl and FeS / FeOCl photocatalysts;
[0019] Figure 3 Shown are SEM images of photocatalysts: (a) FeOCl; (b) FeS / FeOCl;
[0020] Figure 4 The figure shows the performance comparison of powdered FeOCl and FeS / FeOCl catalysts in degrading organic pollutants under sunlight irradiation;
[0021] Figure 5 The figure shows the performance comparison of powdered FeS / FeOCl catalyst in degrading organic pollutants under sunlight irradiation and other different conditions;
[0022] Figure 6 The figure shows the light stability experiment of powdered FeS / FeOCl catalyst for degradation of organic pollutants under sunlight;
[0023] Figure 7 Shown is a photo of supported FeS / FeOCl catalyst;
[0024] Figure 8 Shown is the experimental diagram of the cyclic stability of supported FeS / FeOCl in degrading organic pollutants under simulated solar light. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments and drawings to clearly and completely describe the concept, specific structure and technical effects of the present invention, so as to fully understand the purpose, scheme and effect of the present invention. It should be noted that the embodiments and features in the embodiments of this application can be combined with each other without conflict.
[0026] Example 1
[0027] A method for preparing a powdered FeS / FeOCl photocatalyst comprises the following steps:
[0028] Step 1: 1.622 g of anhydrous FeCl3 was placed in a crucible and calcined at 380 °C for 2.5 h. After calcination, the mixture was cooled to room temperature. The obtained product was centrifuged, washed with deionized water three times, frozen and vacuum dried for 24 h, and ground to obtain FeOCl;
[0029] Step 2: Weigh 0.858 g FeOCl, disperse it in 20 mL water and mix it with 20 mL 0.02 mol / L Na2S solution. After magnetic stirring for 3 h, centrifuge and wash it with water three times, freeze-dry it in a vacuum oven for 24 h, and grind it to obtain a powdered FeS / FeOCl catalyst.
[0030] Example 2
[0031] A method for preparing a supported FeS / FeOCl photocatalyst comprises the following steps:
[0032] Step 1: 1.622 g of anhydrous FeCl3 was placed in a crucible and calcined at 380 °C for 2.5 h. After calcination, the mixture was cooled to room temperature. The obtained product was centrifuged, washed with deionized water three times, frozen and vacuum dried for 24 h, and ground to obtain FeOCl;
[0033] Step 2: Weigh 0.858 g FeOCl, disperse it in 20 mL water and mix it with 20 mL 0.02 mol / L Na2S solution. After magnetic stirring for 3 h, centrifuge and wash it with water for 3 times, freeze-dry it in a vacuum oven for 24 h, and grind it to obtain a powdered FeS / FeOCl catalyst.
[0034] Step 3: Take 10 mg of the powdered FeS / FeOCl catalyst obtained in step 2, disperse it in 0.8 mL of ultrapure water, and then ultrasonically peel it into a thin layer. Then load it on a 2 cm×2 cm frosted glass sheet and dry it at 60℃ for 12 h to obtain a supported FeS / FeOCl catalyst. Figure 7 shown.
[0035] Example 3
[0036] A method for preparing a powdered FeOCl catalyst comprises the following steps:
[0037] 1.622 g of anhydrous FeCl3 was placed in a crucible and heated at 380 °C for 2.5 h. After the reaction was completed, it was cooled to room temperature. The product was centrifuged, washed with deionized water three times, frozen and vacuum dried for 24 h, and ground to obtain a powdered FeOCl catalyst.
[0038] The XRD patterns of the powdered FeOCl and powdered FeS / FeOCl catalysts obtained in Example 3 and Example 1 are shown in Figure 1 , SEM images are shown in Figure 2 The XRD patterns of the samples were obtained ( Figure 1 ) It can be seen that all the diffraction peaks of the powdered FeOCl correspond to the diffraction peaks of FeOCl PDF#24-1005, and there are no impurity peaks, indicating that the prepared powdered FeOCl catalyst has high purity and good crystallinity; and the XRD pattern of the powdered FeS / FeOCl catalyst also has the corresponding peak of FeS PDF#23-1120; Figure 2 The XPS full spectrum of FeOCl and FeS / FeOCl photocatalysts shows the presence of S element in FeS / FeOCl photocatalyst, that is, FeS is in situ generated on FeOCl. Figure 3 From the SEM images of (a) FeOCl and (b) FeS / FeOCl, it can be seen that the FeOCl and FeS / FeOCl photocatalysts prepared by the above method are both plate-like crystals.
[0039] Example 4
[0040] The powdered FeOCl catalyst prepared according to the method steps in Example 3 is used for photocatalytic degradation of organic pollutants, and the specific steps are as follows:
[0041] First, 10 mg of the catalyst was ultrasonically dispersed in 40 mL of 10 mg / L rhodamine B (RhB) solution. After magnetic stirring for 20 min in a dark environment to reach adsorption equilibrium, H2O2 was added to degrade it under sunlight. 3 mL of the sample was taken every 5 min, and the residual concentration was measured at 554 nm using a UV-vis spectrophotometer after centrifugal filtration.
[0042] The formula for the residual amount of organic pollutants is: n=c / c0;
[0043] Where c is the residual concentration of organic pollutants and c0 is the original concentration of organic pollutants. The degradation rate constant is obtained by fitting the natural logarithmic function.
[0044] Example 5
[0045] The powdered FeS / FeOCl catalyst prepared according to the method steps in Example 1 was used in an experiment of photocatalytic degradation of organic pollutants, and the specific steps were as follows:
[0046] First, 10 mg of the catalyst was ultrasonically dispersed in 40 mL of 10 mg / L rhodamine B (RhB) solution. After magnetic stirring for 20 min in a dark environment to reach adsorption equilibrium, H2O2 was added to degrade it under sunlight. 3 mL of the sample was taken every 5 min, and the residual concentration was determined using a UV-vis spectrophotometer after centrifugal filtration.
[0047] The formula for residual organic pollutants is: n=c / c0;
[0048] Where c is the residual concentration of organic pollutants and c0 is the original concentration of organic pollutants. The degradation rate constant is obtained by fitting the natural logarithmic function.
[0049] The two photocatalysts FeOCl and FeS / FeOCl obtained in Example 3 and Example 1 were used for photocatalytic and photo-assisted Fenton degradation of the organic pollutant Rhodamine B. Figure 4 The results show that under the catalysis of FeS / FeOCl, the degradation rate of Rhodamine B can reach 99% within 15 minutes, while that of FeOCl is only 41%. The degradation rate constant of FeS / FeOCl catalyst is 0.5466min -1 , is FeOCl catalyst (0.1606 min -1 ) is 3.4 times.
[0050] Example 6
[0051] The powdered FeS / FeOCl catalyst prepared according to the method steps in Example 1 was used in an experiment of photocatalytic degradation of organic pollutants, and the specific steps were as follows:
[0052] First, 10 mg of the catalyst was ultrasonically dispersed in 40 mL of 50 mg / L ofloxacin solution (OFX). After magnetic stirring for 20 min in a dark environment to reach adsorption equilibrium, H2O2 was added to degrade it under sunlight. 1 mL of the sample was taken every 1 h, filtered, and the ofloxacin concentration was determined by high performance liquid chromatography.
[0053] The formula for residual organic pollutants is: n=c / c0;
[0054] Where c is the residual concentration of organic pollutants and c0 is the original concentration of organic pollutants. The degradation rate constant is obtained by fitting the natural logarithmic function.
[0055] The FeS / FeOCl photocatalyst obtained in Example 1 was dispersed in 40 mL of 50 mg / L ofloxacin solution (OFX), and after magnetic stirring for 20 min in a dark environment to reach adsorption equilibrium, H2O2 was added to perform photo-Fenton degradation under sunlight and a comparative experiment on degradation of organic pollutants under other different conditions was performed, as shown in FIG. Figure 5 As shown. By fitting the natural logarithmic function, it was found that under the conditions of the photo-Fenton reaction catalyzed by FeS / FeOCl, the degradation rate constant was 0.0351 min -1 , is the dark Fenton reaction condition (0.0172 min -1 ) is 2.04 times that of H2O2 under direct sunlight activation (0.0117 min -1 ) is 3 times.
[0056] The FeS / FeOCl photocatalyst obtained in Example 1 was dispersed in 40 mL of 50 mg / L ofloxacin solution (OFX) after being irradiated with sunlight for different durations. After magnetic stirring for 20 min in a dark environment to reach adsorption equilibrium, H2O2 was added to carry out a photo-Fenton degradation experiment of organic pollutants under sunlight. Figure 6 As shown in the figure, after 24 hours of sunlight exposure, the degradation rate still reaches 98% in two hours, and the degradation rate constant is 1.3925 h -1 Compared with the degradation rate constant without light (1.4813 h -1 ) retained 94%, indicating that the FeS / FeOCl catalyst has good stability.
[0057] Example 7
[0058] The supported FeS / FeOCl catalyst obtained in Example 2 was used in the photocatalytic Fenton degradation of organic pollutants experiment, and the specific steps were as follows:
[0059] The supported FeS / FeOCl catalyst was placed in 40 mL of 50 mg / L ofloxacin solution (OFX). After magnetic stirring for 20 min in a dark environment to reach adsorption equilibrium, H2O2 was added and irradiated under a 300 W xenon lamp to simulate sunlight. 1 mL was sampled every 1 h, and the concentration of ofloxacin was determined by high performance liquid chromatography. After 4 h of illumination, the supported catalyst was transferred to another 40 mL of 50 mg / L ofloxacin solution (OFX) for cyclic degradation.
[0060] The formula for the residual amount of organic pollutants is: n=c / c0;
[0061] Where c is the current concentration of organic pollutants and c0 is the original concentration of organic pollutants. The degradation rate constant is obtained by fitting the natural logarithmic function.
[0062] Cyclic degradation of supported FeS / FeOCl catalysts Figure 8 It can be seen that the supported FeS / FeOCl catalyst obtained in Example 2 was used for photocatalytic degradation of organic pollutants for a total of 6 cycles, and the degradation rate of ofloxacin reached more than 96% at 4 h. The average degradation rate constant was 1.2898 h -1 (Standard deviation is 0.3791 h -1 ), the median value is 1.2419 h -1 , the maximum value reaches 2.0154 h -1 , is when using powdered FeS / FeOCl catalyst (2.106 h -1 ).
[0063] In summary, the method for preparing the catalyst of the present invention is simple to operate, low in cost, fast and green and environmentally friendly. The obtained FeS / FeOCl catalyst has enhanced charge transfer efficiency and specific surface area compared to FeOCl, thereby improving photocatalytic and photo-Fenton performances. It is applied in the photocatalytic degradation of organic pollutants and is a more efficient new photocatalyst. The obtained supported FeS / FeOCl catalyst has enhanced catalyst stability and recyclability compared to the powdered FeS / FeOCl catalyst, thereby reducing additional problems in practical applications. It is a more practical, efficient and new photocatalyst.
[0064] Although the description of the present invention has been quite detailed and specifically describes several described embodiments, it is not intended to be limited to any of these details or embodiments or any particular embodiment, but should be regarded as providing a broad possible interpretation of these claims in view of the prior art by reference to the appended claims, thereby effectively covering the intended scope of the present invention. In addition, the above description of the present invention is based on the embodiments foreseeable by the inventor, and its purpose is to provide a useful description, and those non-substantial changes to the present invention that have not yet been foreseen may still represent equivalent changes to the present invention.
Claims
1. Application of a supported FeS / FeOCl photocatalyst in photocatalytic or light-assisted Fenton reaction degradation of organic pollutants, characterized in that: The organic pollutant is at least one of ofloxacin, rhodamine B, bisphenol A, steroidal estrogen, ampicillin antibiotic, parachlorophenol insecticide or 2,4,6-trichlorophenol antibacterial agent; The preparation method of the FeS / FeOCl photocatalyst comprises the following steps: Anhydrous FeCl3 is calcined in air, cooled to room temperature after calcination, centrifuged, washed with water, dried, and ground to obtain FeOCl; FeOCl is then dispersed in water and mixed with Na2S solution for reaction, centrifuged, washed with water, dried, and ground to obtain FeS / FeOCl photocatalyst; The FeS / FeOCl photocatalyst was placed in water and then ultrasonically loaded on a glass substrate to obtain a loaded FeS / FeOCl catalyst.
2. The use according to claim 1, characterized in that: The molar ratio of Na2S to FeOCl is 1:10-20.
3. The use according to claim 2, characterized in that: The molar ratio of Na2S to FeOCl is 1:
20.
4. The use according to claim 1, characterized in that: The calcination temperature was 380 °C and the calcination time was 2.5 h.
5. The use according to claim 1, characterized in that: The reaction time is 3 h.
6. The use according to claim 1, characterized in that: Freeze vacuum drying was used for drying, and the drying time was 24 h.
Citation Information
Patent Citations
Preparation method of Ag2S / Ag3PO4 composite photocatalyst
CN102824921A
Composite FeS-GQDs nanomaterial and preparation method and application thereof
CN110252343A